Analisis Tingkat Pemahaman dan Psikologi Nazhir dalam Penerapan PSAK Syariah 112 Tentang Wakaf - Noviyanti, Noni; Ainulyaqin, MH; Achmad, Listian Indriyani; Mamun, Sukron (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Waqf assets in Indonesia have increased significantly, but the potential of waqf has not been optimized. In Bekasi Regency, the majority of land waqf is focused on places of worship, not yet combined with other functions such as education or the people's economy. Increasing the contribution of waqf requires literacy, regulation, and capacity building of nazir. PSAK 112 is present for good waqf governance, regulating recognition, measurement, presentation, and disclosure of transactions, accountability, and public trust. This study aims to analyze the level of understanding and psychology of nazir in the application of PSAK 112 in Bekasi Regency, especially in the Cikarang area. This research is important because previous research focused on waqf reporting practices, while the current research focuses on the reasons for the low implementation of PSAK 112 by nazir.